Acousto-holographic reconstruction of whole-cell stiffness maps - Varol, Rahmetullah; Karavelioglu, Zeynep; Omeroglu, Sevde; Aydemir, Gizem; Karadag, Aslihan; Meco, Hanife E.; Demircali, Ali A.; Yilmaz, Abdurrahim; Kocal, Gizem C.; Gencoglan, Gulsum; Oruc, Muhammed E.; Esmer, Gokhan B.; et al. (NATURE PORTFOLIO, 2022)
Accurate assessment of cell stiffness distribution is essential due to the critical role of cell mechanobiology in regulation of vital cellular processes like proliferation, adhesion, migration, and motility. Stiffness provides critical information in understanding onset and progress of various diseases, including metastasis and differentiation of cancer. Atomic force microscopy and optical trapping set the gold standard in stiffness measurements. However, their widespread use has been hampered with long processing times, unreliable contact point determination, physical damage to cells, and unsuitability for multiple cell analysis. Here, we demonstrate a simple, fast, label-free, and high-resolution technique using acoustic stimulation and holographic imaging to reconstruct stiffness maps of single cells. We used this acousto-holographic method to determine stiffness maps of HCT116 and CTC-mimicking HCT116 cells and differentiate between them. Our system would enable widespread use of whole-cell stiffness measurements in clinical and research settings for cancer studies, disease modeling, drug testing, and diagnostics. Traditional methods for cell stiffness measurements are limited by long processing times and unsuitability for multiple cell analysis. Here, the authors demonstrate a fast technique based on acoustic stimulation and holographic imaging to reconstruct whole-cell stiffness maps of individual and multiple cells.
Keywords: ATOMIC-FORCE MICROSCOPY; REFRACTIVE-INDEX; LIVING CELLS; DEFORMABILITY; MECHANICS; PRINCIPLES; ALGORITHM; VIABILITY; Science & Technology - Other Topics